Classical instanton solutions in quantum field theory - Shulyakovsky, Roman G.; Gribowsky, Alexander S.; Garkun, Alexander S.; Nevmerzhitsky, Maxim N.; Shaplov, Alexei O.; Shohonov, Denis A. (Journal of the Belarusian State University. Physics, 2020)
Instantons are non-trivial solutions of classical Euclidean equations of motion with a finite action. They provide stationary phase points in the path integral for tunnel amplitude between two topologically distinct vacua. It make them useful in many applications of quantum theory, especially for describing the wave function of systems with a degenerate vacua in the framework of the path integrals formalism. Our goal is to introduce the current situation about research on instantons and prepare for experiments. In this paper we give a review of instanton effects in quantum theory. We find in stanton solutions in some quantum mechanical problems, namely, in the problems of the one-dimensional motion of a particle in two-well and periodic potentials. We describe known instantons in quantum field theory that arise, in particular, in the two-dimensional Abelian Higgs model and in SU(2) Yang – Mills gauge fields. We find instanton solutions of two-dimensional scalar field models with sine-Gordon and double-well potentials in a limited spatial volume. We show that accounting of instantons significantly changes the form of the Yukawa potential for the sine-Gordon model in two dimensions.
Keywords: instanton; quantum theory; quantum mechanics; gauge field; scalar field; confinement